Assessment of knowledge, attitude, and practice toward first aid among female school educators in Riyadh, Saudi Arabia: a cross-sectional study - Abdelrahman, Doaa; Aleyeidi, Nouran Abdullah; Alqahtani, Huda Turki; Aldosari, Falak Nasser; Al Shammari, Tmadher Ghanam; Alrusaini, Norah Khalid; Almahfouz, Rnda Fahad; Altamimi, Sarah Ali; Alshehri, Shatha Abdulwahab; Alsubaie, Rahaf Muqbel; Almuzaini, Raghad Abdulrahman; Innab, Jazil Abdulrahman; et al. (Frontiers in Public Health, 2024)
Objectives School-age children are constantly at risk of unintentional injuries. School educational staff are the primary group responsible for maintaining student welfare and responding to emergency situations. The present study aims to evaluate the knowledge and attitudes, practice level, and contextual factors related to first aid among female educational staff in Riyadh, Saudi Arabia. Methods A cross-sectional study was conducted with a convenience sampling of 1,060 female school staff at all educational levels in Riyadh. Participants completed a self-administered online questionnaire that contained items assessing sociodemographic data, knowledge, attitudes, and practice regarding first aid. Results Most of the 1,060 participants reported above average knowledge level, with a mean score of 21 (max 35). On the other hand, positive attitude toward first aid was high (μ = 22.9; max 25). Approximately 33.4% of staff had previous first aid training, and 79.2% were willing to participate in future trainings. First aid knowledge was highest for choking and lowest for seizures. Conclusion The attitudes toward first aid were generally positive, and the knowledge of first aid was above average among most participants but still unsatisfactory. Mandatory first aid courses are necessary to support children’s health during their education.